ISLAMIC MACROECONOMICS AS AN ALTERNATIVE SYSTEM IN ADDRESSING GLOBAL ECONOMIC CRISES: A BIBLIOMETRIC CO-OCCURRENCE ANALYSIS USING VOSVIEWER - Muhammad Abrar; Azharsyah Ibrahim; Muhammad Arifin; Fithriady Ilyas (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
ABSTRACT Recurring global economic crises have exposed the limitations of conventional economic systems in ensuring stability and economic justice, thereby increasing attention toward Islamic macroeconomics as an alternative framework based on risk sharing, distributive justice, and the integration of the real sector. This study aims to map the development of the Islamic macroeconomics literature in addressing global crises and to identify its thematic structure, research trends, and existing research gaps. This study employs a bibliometric approach using keyword co-occurrence analysis with VOSviewer. The data were obtained from Web of Science covering the period 2000–2025. The initial search yielded 2,710 documents, which were refined to 391 articles for the final analysis using network, overlay, and density visualizations. The findings indicate that the literature is still dominated by themes related to financial system stability and Islamic banking. In contrast, studies on Islamic fiscal policy, Islamic social finance, and the integration of maqāṣid al-sharīʿah at the macroeconomic level remain limited and peripheral. Temporally, there is a shift toward sustainability and distributive justice issues; however, this shift has not been accompanied by strong conceptual integration. These findings suggest that Islamic macroeconomics is still developing in a partial manner. This study recommends the development of a more integrative and application-oriented Islamic macroeconomic model, as well as the strengthening of cross-country empirical research. ABSTRAK Krisis ekonomi global yang berulang menunjukkan keterbatasan sistem ekonomi konvensional dalam menjaga stabilitas dan keadilan ekonomi, sehingga mendorong perhatian terhadap ekonomi makro Islam sebagai alternatif berbasis risk sharing, keadilan distributif, dan keterkaitan sektor riil. Penelitian ini bertujuan memetakan perkembangan literatur ekonomi makro Islam dalam menghadapi krisis global serta mengidentifikasi struktur tematik, tren, dan celah penelitian. Penelitian menggunakan pendekatan bibliometrik melalui analisis co-occurrence kata kunci dengan bantuan VOSviewer. Data diperoleh dari Web of Science pada periode 2000–2025. Pencarian awal menghasilkan 2.710 dokumen yang disaring menjadi 391 artikel untuk analisis akhir melalui network, overlay, dan density visualization. Hasil penelitian menunjukkan bahwa kajian masih didominasi oleh tema stabilitas sistem keuangan dan perbankan Islam, sementara kebijakan fiskal Islam, keuangan sosial, dan integrasi maqāṣid al-sharīʿah pada level makro relatif terbatas dan bersifat periferal. Secara temporal, terdapat pergeseran menuju isu keberlanjutan dan keadilan distributif, namun belum diikuti integrasi konseptual yang kuat. Temuan ini menegaskan bahwa ekonomi makro Islam masih berkembang secara parsial. Penelitian ini merekomendasikan pengembangan model makroekonomi Islam yang integratif dan aplikatif serta penguatan kajian empiris lintas negara.